PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK ANZ INDONESIA - Gita Susanty; Jamaludin Khalid (LPPM Universitas Asa Indonesia, 2016)
Purpose- . Aiming to measure the training and motivation against employee’s performance in P.T. ANZ Bank, Jakarta Design/methology/approach- A questionaire survey to employee’s of P.T. ANZ Bank.The sample were 50, selected by purposive, within a single organization supported by interviews. Data analyzed by multiple regression using SPSS version 20 Findings- Overall tests done, it is concluded that partially, training has effected employee’s performance significantly. The same thing that motivation has effected employee’s performance, significantly. Additionally, both training and motivation, simulataneously, have effected employee’s performance, significantly, too. Research limitations- The limitation of this research lies on its scope of object, and the limited variables involved. It I s then suggested for the next research that other variable such as compensation, and other exogen variable can be deployed too. This results may not be applicable in the same line of business. Practical implications-The manager of human resource shall maintain and develop the potential of employees by providing a combination of training and motivation in human resourcesopment. The Originality-This is done exclusively for the P.T. ANZ Bank as a single company that may applicable therein.